Branding SMEs as Competitiveness in the Era of ASEAN Economic Community - Raden, A Z M; Listya, A; Maya, S (KnE Social Sciences, 2018)
ASEAN Economic Community that was applied at the beginning of the year 2016 has provided opportunities for Indonesia in becoming a good investment and business destination for other countries. The way to be a business part of them are through Small and Medium Enterprises. To bring forward the Small and Medium Enterprises, they are needed to be reviewed externally by the government-made policies that will reinforce the Small and Medium Enterprises and internally to strengthen the potential of the existing ones through branding. This research of branding can be used as reference for the Small and Medium Enterprises in developing the concept of branding on their business to be more competitive in the era of ASEAN Economic Community. The research uses a case-study approach to several Small and Medium Enterprises as the Partners of KSPP Sharia Tadbiirul Ummah by applying the theory of branding. The result shows that they do not have uniqueness in their brands even though its product has superiority. Branding of the Small and Medium Enterprises have not yet been maximal. Therefore, we do the branding for several Small and Medium Enterprises as the Partners of KSPP Sharia Tadbiirul Ummah as the recommendations of this research. Keywords: branding, the small and medium enterprises, the AEC